Voluntary physical exercise protects against behavioral and endocrine reactivity to social and environmental stressors in the prairie vole. (3rd September 2018) - Watanasriyakul, W. Tang; Wardwell, Joshua; McNeal, Neal; Schultz, Rachel; Woodbury, Matthew; Dagner, Ashley; Cox, Miranda; Grippo, Angela J.
ABSTRACT: Physical activity can combat detrimental effects of stress. The current study examined the potential protective effects of exercise against a combination of social isolation and chronic mild stress (CMS) in a prairie vole model. Female voles were isolated for 4 weeks, with the addition of CMS during the final 2 weeks. Half of the voles were allowed access to a running wheel during this final 2 weeks, while the other half remained sedentary. Animals underwent behavioral tests to assess depressive- and anxiety-behaviors. In a subset of animals, plasma was collected 10 minutes after behavioral testing for corticosterone analysis. In a separate subset, brains were collected 2 hours after behavioral testing for cFos analysis in the paraventricular nucleus (PVN). Voles in the exercise group displayed significantly lower depressive- and anxiety-behaviors, and displayed significantly lower corticosterone levels, compared to animals in the sedentary group. There was no difference in PVN cFos activity between groups. Interestingly, animals that moderately exercised displayed lower levels of depressive-behavior and attenuated corticosterone reactivity compared to animals in the low and high activity subgroups. These findings suggest that physical activity can protect against a combination of social and environmental stressors.